Constructive entrepreneurship as a mechanism of overcoming risks of negative impact of economic sanctions - V. M. Yakovlev (Путеводитель предпринимателя)
The article deals with the problems ofrisk and the growth of economic security of economic entities and the economy of Russia in the context of the crisis trend under the influence of economic proto nerve market, as well as foreign economic restrictions-sanctions. In order to prevent these negative trends, the author reveals the essence and importance of the Russian business activities to identify and strain the resulting Mile gross socio-economic development of the economic and society. Along with this, the ways of formation of the organization and economic mechanisms to eliminate the risks arising on this basis are considered, along with the wrote additional measures to ensure the economic security of economic entities and life support of citizens.